Laser irradiated phenothiazines: New potential treatment for COVID-19 explored by molecular docking - Udrea, Ana-Maria; Avram, Speranta; Nistorescu, Simona; Pascu, Mihail-Lucian; Romanitan, Mihaela Oana (Journal of photochemistry and photobiology. B, Biology, 2020)
The worldwide infection with the new Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) demands urgently new potent treatment(s). In this study we predict, using molecular docking, the binding affinity of 15 phenothiazines (antihistaminic and antipsychotic drugs) when interacting with the main protease (Mpro) of SARS-CoV-2. Additionally, we tested the binding affinity of photoproducts identified after irradiation of phenothiazines with Nd:YAG laser beam at 266 nm respectively 355 nm. Our results reveal that thioridazine and its identified photoproducts (mesoridazine and sulforidazine) have high biological activity on the virus Mpro. This shows that thioridazine and its two photoproducts might represent new potent medicines to be used for treatment in this outbreak. Such results recommend these medicines for further tests on cell cultures infected with SARS-CoV-2 or animal model. The transition to human subjects of the suggested treatment will be smooth due to the fact that the drugs are already available on the market. [Display omitted] •Binding affinity of 15 phenothiazines with the main protease (Mpro) of SARS-CoV-2 is predicted by molecular docking.•We test the binding affinity of photoproducts identified after irradiation of phenothiazines with Nd:YAG laser beam.•Thioridazine and its photoproducts, mesoridazine and sulforidazine, have high biological activity on the virus Mpro.•Results recommend these medicines for further tests on cell cultures infected with SARS-CoV-2 or animal model.